Flexible Pricing Models for Cloud Services - Bello, Sururah A.; Abdul Wakil, Gazali (Discoveries in Agriculture and Food Sciences, 2014)
Cloud Computing's service models IaaS and PaaS have a number of proprietary pricing models as the services has been commoditized to some extent. The SaaS so far has been known with a flat price within the usage time. But pricing models need to be more flexible to prevent customers from thinking that paying same price for a service over a period is no more cost effective, in spite of the level of utilization of the service. For Cloud Computing this has to be taken into account. Africans are not used to fixed price models in their business transactions. In order to expand the acceptability of Cloud Computing to African a means of disputing prices is necessary.  This study proposes cloud utility price models to give the Cloud customer the luxury of different usage style and determine a customer specific, individual, most suitable price model. It gives the customer the opportunity to choose a price model for the predicted usage and work within the budget. The proposed cloud utility price models presented using use cases.